The assessment of the quality of human resources in the midwife profession in the healthcare sector of the Czech Republic - Erika Urbánková; Petra Hospodková; Lucie Severová (Economies, 2018)
The objective of this paper is the assessment of the current state of employment in the midwife profession in the health and social care sector, especially from the viewpoint of quality assurance. Primary research focuses on the level of practical and theoretical knowledge and the skills of graduates within the last 10 years, as well as the forms of development of human resources that healthcare facilities offer for the purposes of supplementing knowledge and developing skills that are lacking. The quantitative research took place in private and public healthcare facilities in the Czech Republic in 2017. The results of the quantitative research show that the offers of workers in the midwife profession in the labor market are slightly insufficient in relation to demand. Research results show that the overall educational level of graduates has improved over time. The research also shows that the greatest deficiencies in terms of missing competencies among new graduates are seen in the area of expertise according to Regulation No. 55/2011 Coll. (newly No. 2/2016), and that what the graduates lack most are skills in communicating with patients. Conversely, current graduates are better equipped with language skills, computer skills and time-management ability. The research also shows that overall practical readiness lags far behind theoretical readiness.
Keywords: I11; J; O15; 330; Czech Republic; healthcare; midwife; human resources quality and development; graduates; cluster analysis